Plan Quality and Treatment Efficiency for Radiosurgery to Multiple Brain Metastases: Non-Coplanar RapidArc vs. Gamma Knife - Liu, Haisong; Andrews, David W.; Evans, James J.; Werner-Wasik, Maria; Yu, Yan; Dicker, Adam Paul; Shi, Wenyin (Frontiers in Oncology, 2016)
Objectives This study compares the dosimetry and efficiency of two modern radiosurgery [stereotactic radiosurgery (SRS)] modalities for multiple brain metastases [Gamma Knife (GK) and LINAC-based RapidArc/volumetric modulated arc therapy], with a special focus on the comparison of low-dose spread. Methods Six patients with three or four small brain metastases were used in this study. The size of targets varied from 0.1 to 10.5 cc. SRS doses were prescribed according to the size of lesions. SRS plans were made using both Gamma Knife® Perfexion and a single-isocenter, multiple non-coplanar RapidArc®. Dosimetric parameters analyzed included RTOG conformity index (CI), gradient index (GI), 12 Gy isodose volume (V12Gy) for each target, and the dose “spread” (Dspread) for each plan. Dspread reflects SRS plan’s capability of confining radiation to within the local vicinity of the lesion and to not spread out to the surrounding normal brain tissues. Each plan has a dose (Dspread), such that once dose decreases below Dspread (on total tissue dose–volume histogram), isodose volume starts increasing dramatically. Dspread is defined as that dose when volume increase first exceeds 20 cc/0.1 Gy dose decrease. Results RapidArc SRS has smaller CI (1.19 ± 0.14 vs. 1.50 ± 0.16, p < 0.001) and larger GI (4.77 ± 1.49 vs. 3.65 ± 0.98, p < 0.01). V12Gy results were comparable (2.73 ± 1.38 vs. 3.06 ± 2.20 cc, p = 0.58). Moderate to lower dose spread, V6, V4.5, and V3, were also equivalent. GK plans achieved better very low-dose spread (≤3 Gy) and also had slightly smaller Dspread, 1.9 vs. 2.5 Gy. Total treatment time for GK is estimated between 60 and 100 min. GK treatments are between 3 and 5 times longer compared to RapidArc treatment techniques. Conclusion Dosimetric parameters reflecting prescription dose conformality (CI), dose fall off (GI), radiation necrosis indicator (V12Gy), and dose spread (Dspread) were compared between GK SRS and RapidArc SRS for multi-mets. RapidArc plans have smaller CI but larger GI. V12Gy are comparable. GK appears better at reducing only very low-dose spread (<3 Gy). The treatment time of RapidArc SRS is significantly reduced compared to GK SRS.